2021
DOI: 10.1016/j.redox.2021.102152
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin deficiency renders mice susceptible to hepatic steatosis in the absence of insulin resistance

Abstract: Background & aims Plasma concentrations of bilirubin, a product of heme catabolism formed by biliverdin reductase A (BVRA), inversely associate with the risk of metabolic diseases including hepatic steatosis and diabetes mellitus in humans. Bilirubin has antioxidant and anti-inflammatory activities and may also regulate insulin signaling and peroxisome proliferator-activated receptor alpha (PPARα) activity. However, a causal link between bilirubin and metabolic diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…In this same study, low HO-1 mRNA levels in human liver transplants correlated with increased expression of M1 pro-inflammatory markers [ 48 , 49 ]. Liver-specific biliverdin reductase A (BVRA) knockout animals with reduced hepatic bilirubin had worsened fatty liver on a high-fat diet compared to littermate controls [ 50 ], which was confirmed in global BVRA knockout animals [ 51 ]. Bilirubin reduces lipid content and inflammatory markers in mouse models of obesity-induced NAFLD [ 46 , 47 ].…”
Section: Ho-1 Bvra and Bilirubin As Inflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this same study, low HO-1 mRNA levels in human liver transplants correlated with increased expression of M1 pro-inflammatory markers [ 48 , 49 ]. Liver-specific biliverdin reductase A (BVRA) knockout animals with reduced hepatic bilirubin had worsened fatty liver on a high-fat diet compared to littermate controls [ 50 ], which was confirmed in global BVRA knockout animals [ 51 ]. Bilirubin reduces lipid content and inflammatory markers in mouse models of obesity-induced NAFLD [ 46 , 47 ].…”
Section: Ho-1 Bvra and Bilirubin As Inflammatory Mediatorsmentioning
confidence: 99%
“…While there are limited studies showing that BVRA is regulated by exercise [ 70 ], there have been supporting studies showing a role for the enzyme in metabolism [ 50 , 51 , 124 , 125 , 127 ]. Adipocyte-specific deletion of BVRA results in adipocyte hypertrophy and increased inflammation while decreasing mitochondrial number and markers of adipocyte browning such as PPARα and β3 adrenergic receptor ( Adrb3 ) [ 127 ].…”
Section: The Signaling Mechanisms Of Heme Oxygenase and Bilirubin In ...mentioning
confidence: 99%
“…There is a basic research showed that bilirubin deficiency renders mice susceptible to hepatic steatosis in the absence of insulin resistance. It adopted a kind of contrarian strategy to prove that the pathogenesis of MetS and NAFLD is not exactly identically ( 57 ). In addition, the variety of definitions of MetS and the variety of diagnostic methods for NAFLD in different studies is also make it challenging that assess the consistent-association of serum bilirubin with MetS and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The observed discrepancy suggests that insulin signaling seems less affected in global Bvra -deficient mice, fed a chow diet, than in liver-specific Bvra -deficient animals. Bvra −/− mice, fed with a high-fat diet, have comparable fasted plasma glucose and insulin, glucose and insulin tolerance, glucose uptake, as well as insulin signaling, but developed a fatty and inflamed liver as a result of enhanced oxidative stress reflected in increased non-enzymatic lipid peroxidation [ 74 ]. Thus, in the context of Bvra −/− Ugt1 −/− and Ugt1 −/− mice, further studies with more specific glucose and diet challenges may be needed to reach more definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%